2012
DOI: 10.4149/neo_2012_087
|View full text |Cite
|
Sign up to set email alerts
|

Human Lung Cancer cell line SPC-A1 contains cells with characteristics of cancer stem cells

Abstract: Cancer stem cells (CSCs) play important roles in occurrence, development, recurrence and metastasis of cancer. Isolation and identification of CSCs have been performed from some cancer tissues or cells. In this paper, human lung adenocarcinoma stem cells were induced and isolated from SPC-A1 cells and their characteristics were determined. SPC-A1 cells were cultured in serum-free medium and epidermal growth factor and basic fibroblast growth factor were added into the medium to induce the formation of multicel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…This model has been used to study the expression profile of stem cell signalling in CD133 high /CD44 high prostate cancer stem cells and glioblastoma tumor‐initiating cells (Oktem et al , ). Additionally, this technique has demonstrated that human lung cancer cell line SPC‐A1 contains a subpopulation of CSCs (Zhou, Yang & Li, ).…”
Section: Three‐dimensional Cancer Stem Cell Culture Systemsmentioning
confidence: 99%
“…This model has been used to study the expression profile of stem cell signalling in CD133 high /CD44 high prostate cancer stem cells and glioblastoma tumor‐initiating cells (Oktem et al , ). Additionally, this technique has demonstrated that human lung cancer cell line SPC‐A1 contains a subpopulation of CSCs (Zhou, Yang & Li, ).…”
Section: Three‐dimensional Cancer Stem Cell Culture Systemsmentioning
confidence: 99%
“…In A549 cells, the expression of miR-145-5p was suppressed when BMI1 was highly expressed ( Figure 4 B). It has been found that the expression of miR-145 was negatively correlated with high expression of BMI1 in CSCs derived from SPC-A1 lung cancer cells [ 37 ]. In colorectal cancer cells, epigallocatechin-3-gallate, a polyphenol phytochemical, was discovered to inhibit the expression of Notch, BMI1, and EZH2 with an upregulation of the expression of miR-145, miR-34a, and miR-200c, thus reducing tumor growth [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been confirmed that miR-145 has a tumor suppressor function (22,23). miR-145 had a lower level of expression in lung, breast, prostate and colorectal cancer cells (24)(25)(26). However, it is unclear why miR-145 is downregulated in these tumor cells.…”
Section: Discussionmentioning
confidence: 99%